2016
DOI: 10.1002/qj.2702
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid‐scale cloud–radiation feedback for theBetts–Miller–Janjić convection scheme

Abstract: Cloud-radiation feedbacks play a crucial role in the climate system and continue to be a major source of uncertainty in global climate model projections. Despite its importance for regional and local circulations, these feedback processes are not included in subgrid-scale convective parametrizations used in regional weather and climate models, in particular in adjustment schemes that, as opposed to mass-flux schemes, do not deal with convective condensates. Here we present a cloud scheme developed for the Bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
(83 reference statements)
0
17
0
Order By: Relevance
“…Cumulus convection is parameterised using the Betts-Miller-Janjić (BMJ; Janjić 1994) scheme. The precipitating convective cloud scheme developed for the BMJ by Koh and Fonseca (2016) is applied in order to account for cumulus cloud-radiation feedbacks. In all experiments, seasonally dependent vegetation fraction and surface albedo are used.…”
Section: Model Datasets and Diagnosticsmentioning
confidence: 99%
“…Cumulus convection is parameterised using the Betts-Miller-Janjić (BMJ; Janjić 1994) scheme. The precipitating convective cloud scheme developed for the BMJ by Koh and Fonseca (2016) is applied in order to account for cumulus cloud-radiation feedbacks. In all experiments, seasonally dependent vegetation fraction and surface albedo are used.…”
Section: Model Datasets and Diagnosticsmentioning
confidence: 99%
“…TC = tropical cyclone. Kobayashi (2007) found that the CER for precipitation clouds is always larger than that of nonprecipitation clouds. The decrease of CER in the decay stage indicates that there is less precipitation when TC makes a landfall.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 95%
“…And the TC cloud system (TCCS) is also a key factor in climate modulation system (Balaguru et al, ; Mei et al, ; Sriver & Huber, ). As a large‐scale cloud system, it reflects the shortwave radiation from the sun and emits the long‐wave radiation, which controls the fluctuation of atmospheric temperature (Koh & Fonseca, ; Pithan et al, ; Stephens & Wong, ). Also, from a climate dynamic standpoint (Li et al, ), TCCS is particularly important for the accurate representation of numerical simulations for the cloud distribution and radiation globally (Houze, ).…”
Section: Introductionmentioning
confidence: 99%
“…The following physics parameterization schemes were used in the model runs: the Yonsei University Planetary Boundary Layer (PBL) scheme (Hong et al, 2006) with a topographic correction for surface winds to represent the extra drag from subgrid topography and enhanced flow at hill tops following Jiménez and Dudhia (2012); Monin-Obukhov surface layer parameterization (Monin and Obukhov, 1954); the four-layer Noah LSM (Chen and Dudhia, 2001); the Rapid Radiative Transfer Model for Global models (RRTMG) for short-wave and long-wave radiation (Iacono et al, 2008) with a climatological aerosol distribution (Tegen et al, 1997); the Goddard 6-class microphysics scheme (Tao et al, 1989); the Betts-Miller-Janjić cumulus scheme (BMJ; Janjić, 1994) adapted for the tropics (Fonseca et al, 2019) with cumulus cloud-radiation feedbacks accounted for by a precipitating convective cloud scheme (Koh and Fonseca, 2016). The Noah LSM is also initialized with CFSR data.…”
Section: Wrf Simulationsmentioning
confidence: 99%